Screening In silico Antidepressant Activity of Aqueous Extract of Leaves of Rumex acetosa L. - Shareef, Mohd Mohiuddin; Bhavya, E. (Trends in Sciences, 2023)
The main objective of this study is to obtain extracts of Rumex acetosa leaves using various solvents, characterize these extracts and finally evaluate in silico antidepressant activity. Rumex acetosa belongs to polygonaceae family and is often called sorrel. This plant’s leaves were gathered and extracted using a variety of solvents including petroleum ether, ethyl acetate, ethanol, chloroform, and ultimately water. All these extracts are explored to check for various phytoconstituents by commonly used phytochemical screening methods. It was found that aqueous extract of Rumex acetosa (AERA) contained many phytoconstituents like alkaloids, flavonoids, glycosides, and anthocyanins. This aqueous extract was further screened by FTIR, HPLC, and GCMS analysis techniques. In FTIR analysis, aqueous extract of Rumex acetosa showed peaks at 1163.11and 1060.88 cm−1corresponding to anthocyanins. HPLC analysis showed the presence of peaks with the retention time of 6.75, 18.94, 25.19, 28.04, 34.72 and 39.37 min corresponding to sennoside, aloe-emodin, rhein, emodin, chrysophanol, and physcion respectively. In GCMS analysis, peaks at 18.15, 18.50, 20.32, 20.48 and 24.99 correspond to rhein, dibutyl phthalate, emodin, octadecanoic acid, and chrysophanol respectively. Five phytoconstituents - aloe-emodin, chrysophanol, emodin, physcion, and rhein - are further assessed for in silico antidepressant effectiveness based on characterization data. As rhein has the highest negative value of glide energy, it indicates a stronger binding affinity for MAO-A than all other screened constituents. Thus, the study concludes regarding in silico anti-depressant activity against MAO-A. Further, present research puts forth a way to carry out the isolation of therapeutically proven phytoconstituents and to evaluate these constituents for their biological activity. HIGHLIGHTS In FTIR analysis, absorption peaks belonging to C=C, C-H aromatic ring and O-H bonds were found at 1,467-1,431 cm−1, 3,049 and 3,162.71 cm−1 respectively in AERA HPLC analysis showed the presence of peaks with the retention time of 6.75, 18.94, 25.19, 28.04, 34.72 and 39.37 min corresponding to sennoside, aloe-emodin, rhein¸ emodin, chrysophanol, and physcion, respectively In GCMS analysis, peaks at 18.15, 18.50, 20.32, 20.48 and 24.99 correspond to rhein, dibutyl phthalate, emodin, octadecanoic acid, and chrysophanol, respectively Five phytoconstituents viz., aloe-emodin, chrysophanol, emodin, physcion, and rhein, are assessed for in silico antidepressant effectiveness and rhein has the highest negative value of glide energy, it indicates a stronger binding affinity for MAO-A than all other screened constituents GRAPHICAL ABSTRACT